March 15th, 2015, 10:49 AM  #1 
Newbie Joined: Feb 2015 From: canada Posts: 10 Thanks: 0  simplify
y= 4(x1+√2) (x1√2) I got y= 4(x1)^22 In the answer key it says y= 4(x^22x1) who is right and please show why Last edited by rrosa522; March 15th, 2015 at 11:18 AM. 
March 15th, 2015, 11:12 AM  #2 
Global Moderator Joined: Dec 2006 Posts: 20,931 Thanks: 2205 
Did you mean y = 4(x  1 + √2) (x  1  √2)? In that case, y = 4((x  1)²  2) = 4(x²  2x  1). 
March 16th, 2015, 09:16 PM  #3 
Newbie Joined: Mar 2015 From: sri lanka Posts: 2 Thanks: 0 
y=4(x1+√2)(x1√2) y=(4x+44√2)(x1√2) y=(4x²+4x+4√2x+4x44√24√2x+4√2+4) y=(4x²+8x) y=4x(x+2) 
March 17th, 2015, 04:46 AM  #4 
Math Team Joined: Jul 2011 From: Texas Posts: 3,002 Thanks: 1588  
March 17th, 2015, 07:05 PM  #5 
Math Team Joined: Jan 2015 From: Alabama Posts: 3,264 Thanks: 902  
March 17th, 2015, 08:00 PM  #6 
Senior Member Joined: Nov 2010 From: Indonesia Posts: 2,001 Thanks: 132 Math Focus: Trigonometry  The answer key is right. Your mistake was you didn't put brackets after the expansion. You should get y = 4((x1)^22) instead of y = 4(x1)^22.


Tags 
simplify 
Thread Tools  
Display Modes  

Similar Threads  
Thread  Thread Starter  Forum  Replies  Last Post 
Simplify  jiasyuen  Algebra  2  March 11th, 2015 04:30 PM 
Simplify  girlbadatmath  Algebra  3  August 16th, 2014 12:09 AM 
Simplify  The  Algebra  8  April 25th, 2014 06:36 PM 
How to simplify this  Ronaldo  Calculus  1  December 27th, 2012 07:56 AM 
Simplify  Valar30  Algebra  4  June 11th, 2011 09:56 PM 